2016
DOI: 10.1002/jmri.25267
|View full text |Cite
|
Sign up to set email alerts
|

3T MRI investigation of cardiac left ventricular structure and function in a UK population: The tayside screening for the prevention of cardiac events (TASCFORCE) study

Abstract: PurposeTo scan a volunteer population using 3.0T magnetic resonance imaging (MRI). MRI of the left ventricular (LV) structure and function in healthy volunteers has been reported extensively at 1.5T.Materials and MethodsA population of 1528 volunteers was scanned. A standardized approach was taken to acquire steady‐state free precession (SSFP) LV data in the short‐axis plane, and images were quantified using commercial software. Six observers undertook the segmentation analysis.ResultsMean values (±standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(50 reference statements)
0
13
0
Order By: Relevance
“… n number of study subjects included in the weighted mean values, mean p pooled weighted mean, SD p pooled standard deviation, LV left ventricular, EDV end-diastolic volume, ESV end-systolic volume, SV stroke volume, EF ejection fraction, LV M left ventricular mass, CO cardiac output, CI cardiac index, BSA body surface area a Pooled weighted values from references [ 15 , 16 , 19 , 23 , 25 ] b Pooled weighted values from references [ 15 , 16 , 18 , 19 , 23 , 25 ] c Pooled weighted values from references [ 16 , 18 , 19 , 23 , 25 ] d Pooled weighted values from references [ 15 , 23 , 25 ] e Pooled weighted values from references [ 23 , 25 ] f Pooled weighted values from references [ 16 , 25 ] g Calculated as mean p ± 2*SD p …”
Section: Left Ventricular Dimensions and Functions In The Adultmentioning
confidence: 99%
See 1 more Smart Citation
“… n number of study subjects included in the weighted mean values, mean p pooled weighted mean, SD p pooled standard deviation, LV left ventricular, EDV end-diastolic volume, ESV end-systolic volume, SV stroke volume, EF ejection fraction, LV M left ventricular mass, CO cardiac output, CI cardiac index, BSA body surface area a Pooled weighted values from references [ 15 , 16 , 19 , 23 , 25 ] b Pooled weighted values from references [ 15 , 16 , 18 , 19 , 23 , 25 ] c Pooled weighted values from references [ 16 , 18 , 19 , 23 , 25 ] d Pooled weighted values from references [ 15 , 23 , 25 ] e Pooled weighted values from references [ 23 , 25 ] f Pooled weighted values from references [ 16 , 25 ] g Calculated as mean p ± 2*SD p …”
Section: Left Ventricular Dimensions and Functions In The Adultmentioning
confidence: 99%
“…In addition, a full description of the subject cohort (including the analysis methods used), age and gender of subjects was required to be included for this review. Two studies [ 18 , 19 ] included papillary muscles in LV volume except if directly attached to the LV wall, in which case they were included in LV mass (LVM) instead. Since this approach was inconsistent with post-processing recommended by SCMR [ 9 ] and other manuscripts on the topic, both studies were excluded from the current analysis.…”
Section: Left Ventricular Dimensions and Functions In The Adultmentioning
confidence: 99%
“…The rationale, study design, techniques, and population demographics of each of these have been described in detail previously. 8 10 These prior studies and the current study have been approved by an institutional review committee, with all subjects providing written informed consent. The study was performed in adherence with the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work in 306 seventy-year-olds in the PIVUS (Prospective Investigation of the Vasculature in Uppsala Seniors) study found a correlation between the total atherosclerotic burden as measured on whole body angiography and the carotid arterial distensibility and the stroke-volume to pulse pressure ratio [ 22 ]. However this study suffered from several limitations: it did not stratify by sex, a known confounder for stroke volume and pulse pressure; and did not index the stroke volume thus opening the study to significant confounding from body size [ 18 ]. Indeed previous work has shown compliance calculated using indexed SV but not unadjusted SV to be an independent predictor for cardiovascular events demonstrating the importance of these adjustments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Scottish Index of Multiple Deprivation (SIMD) [ 17 ] was treated as a continuous variable within the model. Due to the known significant differences in cardiac mass and volumes between genders, analysis was conducted separately for men and women [ 18 ]. As the hypertension guidelines have changed substantially since the study was conceived when a blood pressure of < 145/95 was considered normotensive, a sensitivity analysis was performed to determine if the results hold true in a cohort who would continue to be considered normotensive according to the 2017 AHA/ACC guidelines (BP < 120/80) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%